Calligraphic solar cells: acknowledging paper and pencil. Issue 17 (23rd August 2016) - Dasari, Mallika; Rajasekaran, Pradeep Ramiah; Iyer, Ratnasabapathy; Kohli, Punit
Abstract: Abstract : We demonstrate fabrication and characterization of photovoltaic (PV) devices made using pencil, paper, and commonly available economical chemicals with a power conversion efficiency of ∼1.8%. The current collecting electrode of the device composed of multilayered graphene (MuLG) was hand-drawn on the cellulosic paper using an H2B pencil. CdSe quantum dots (QD) were used for charge generation, and 3, 4, 9, 10-perylenetetracarboxylic dianhydride (PTCDA) as a bridging molecule to facilitate transfer of the photo-induced charges to the electrodes through MuLG. MuLG acted both as charge carrier and current collector electrode. The device fabrication and testing were accomplished in a wet lab under ambient conditions with minimum use of sophisticated instrumentation. The materials and devices were characterized using UV–visible, fluorescence, x-ray diffraction spectroscopy, and scanning and transmission electron microscopy. I – V characteristics of the PV devices fabricated on paper and polyester transparency substrates were performed using a solar simulator (AM 1.5) under ambient wet laboratory conditions. The use of pencil and paper makes the device fabrication simple, environmentally responsible, and accessible to layperson thus opening a new window for low cost PV and opto-electronic devices.